Tumor suppressor function of laminin-binding α-dystroglycan requires a distinct β3-N-acetylglucosaminyltransferase - Bao, Xingfeng (National Academy of Sciences, 2009)
α-Dystroglycan (α-DG) represents a highly glycosylated cell surface molecule that is expressed in the epithelial cell-basement membrane (BM) interface and plays an essential role in epithelium development and tissue organization. The α-DG–mediated epithelial cell-BM interaction is often impaired in invasive carcinomas, yet roles and underlying mechanisms of such an impaired interaction in tumor progression remain unclear. We report here a suppressor function of laminin-binding glycans on α-DG in tumor progression. In aggressive prostate and breast carcinoma cell lines, laminin-binding glycans are dramatically decreased, although the amount of α-DG and β-dystroglycan is maintained. The decrease of laminin-binding glycans and consequent increased cell migration were associated with the decreased expression of β3-N-acetylglucosaminyltransferase-1 (β3GnT1). Forced expression of β3GnT1 in aggressive cancer cells restored the laminin-binding glycans and decreased tumor formation. β3GnT1 was found to be required for laminin-binding glycan synthesis through formation of a complex with LARGE, thus regulating the function of LARGE. Interaction of the laminin-binding glycans with laminin and other adhesive molecules in BM attenuates tumor cell migratory potential by antagonizing ERK/AKT phosphorylation induced by the components in the ECM. These results identify a previously undescribed role of carbohydrate-dependent cell-BM interaction in tumor suppression and its control by β3GnT1 and LARGE.